Severe tricuspid regurgitation and transcatheter bicaval valves system implantation. Importance of the load to indication - Serra, Walter; Palumbo, Alessandro; Agostinelli, Andrea; Tadonio, Iacopo; Coli, Stefano; Vignali, Luigi (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: To date, there is some specific evidence or criteria supporting the selection of patients with PH and severe tricuspid valve regurgitation that can be initiated to correct tricuspid valvulopathy. Studying the load on the right ventricle and the interaction between the ventricle, valve, and pulmonary artery could be the key to detecting such patients. Methods: Case Report V.M.,Female 83 years old Previous replacement of mitral valve with mechanical prosthesis and precapillary pulmonary hypertension associated with severe tricuspid regurgitation. The patient was in NYHA class III, with lower limb edemas and signs of liver congestion, with severe tricuspid regurgitation associated with mild pulmonary hypertension and sPAP/PAAT Ratio was 0,6 in a specific therapy. It has been necessary to involve the heart team in evaluating a percutaneous interventional treatment, also considering the patient’s comorbidities, which do not lead to cardiac surgery. A bicaval device was implanted. Results: After implantation, the patient was given low doses of dobutamine for three days. At the Cardiac TC control, the dimensions of the IVC were reduced (30mm from 41mm) while at TTE control the hepatic vein backflow did not occur and the oscillation of the leaflets was normal, PAAT 92msc; sPAP/PAAT ratio 0,43, TR grade III. Conclusions: The management of patients with severe symptomatic tricuspid regurgitation remains extremely challenging for the Cardiac Heart Team. The patient’s selection, the ventricular-arterial coupling, and the type of device, depending on the anatomic functional conditions, are still challenging factors